Efficacy and safety of glucosaminylmuramyl dipeptide in treatment of human papillomavirus-associated diseases: a systematic review - A. D. Makatsariya; V. O. Bitsadze; J. Kh. Khizroeva; G. Kh. Vikulov; M. A. Gomberg; A. A. Khryanin (Акушерство, гинекология и репродукция, 2019)
Introduction. Human papillomavirus infection (HPV-infection) remains one of the most important health problems as it significantly reduces the quality of life and stigmatizes the patients. Also, the prevalence of cervical cancer – the most severe outcome of the HPV-infection is 5 % of the global burden of cancer. Although vaccination against human papillomavirus has been proved efficient, its availability in Russia continues to be limited. Therefore, it is important to review other methods of HPV-infection control. A number of studies have confirmed the efficacy of glucosaminylmuramyl dipeptide (GMDP) in the treatment of diseases associated with HPV-infection, but no systematic evaluation of these studies has been published in the available literature.Aim: to analyze the data on the efficacy and safety of GMDP in the treatment of diseases and conditions associated with HPVinfection.Materials and methods. We used the PRISMA approach. The search for the relevant publications was conducted in international scientific databases: the Scientific Electronic Library, the Google Scholar, the ScienceDirect, the Cochrane Community Library, the Pubmed/MEDLINE, and clinical research registries. For this systematic analysis, only full-text publications were used. We evaluated the reliability of evidence and the methodological quality of the studies.Results. We used the following search queries: "glucosaminyl-muramyl dipeptide", "glucosamine L'muramyl dipeptide", "H-acetylglucosaminyl-H-acetylmuramyl dipeptide", "GMDP", "Licopid" (both in Russian and English transcriptions). Based on the results of the screening, 14 full-text publications were selected. At the final stage, review articles with secondary data were excluded; also excluded were original articles published in doubtful resources and those with an unclear status of peer reviewing. This systematic analysis includes 7 publications of acceptable methodological quality. Here, we summarize the consistent conclusions derived from these reports: the addition of therapy with GMDP to local (surgical) methods increases the efficacy of treatment and the duration of remission; destruction of condylomas is more effective when combined with the course of GMDP as compared to using the local destruction alone; GMDP enhances the production of cytokines that have a direct antiviral and antiproliferative effect in HPV-infection (interleukin-1, tumor necrosis factor alpha, gamma-interferon); GMDP causes normalization of cellular and humoral immunity (T-lymphocytes, T-cytotoxic lymphocytes, B-lymphocytes, CD3+, CD4+, CD8+, CD16+, and CD72+ lymphocytes, as well as the production of serum immunoglobulins IgA, IgG, and IgM). A high safety profile of GMDP is evidenced from the absence of reports on adverse events.Discussion. The recommendation for the inclusion of GMDP into a comprehensive treatment for HPV-infection in addition to local interventions is a strong recommendation. The differences between the Russian and international approaches can be explained by the difference in the available resources and funding. We propose to test whether using GMDP for reducing the risk of recurrent HPV-infection is beneficial in terms of pharmacoeconomics. Conclusion. The high efficacy and safety of GMDP in the combined therapy of HPV-infection has been confirmed. Further carefully designed studies on GMDP are needed.